Recent advances in heteroatom-doped graphene quantum dots for sensing applications. Issue 41 (23rd July 2021) - Sohal, Neeraj; Maity, Banibrata; Basu, Soumen
Abstract : Graphene quantum dots (GQDs) are carbon-based fluorescent nanomaterials having various applications due to attractive properties. Abstract : Graphene quantum dots (GQDs) are carbon-based fluorescent nanomaterials having various applications due to attractive properties. But the low photoluminescence (PL) yield and monochromatic PL behavior of GQDs put limitations on their real-time applications. Therefore, heteroatom doping of GQDs is recognized as the best approach to modify the optical as well as electronic properties of GQDs by modifying their chemical composition and electronic structure. In this review, the new strategies for preparing the heteroatom (N, B, S, P) doped GQDs by using different precursors and methods are discussed in detail. The particle size, emission wavelength, PL emissive color, and quantum yield of recently developed heteroatom doped GQDs are reported in this article. The investigation of structure, crystalline nature, and composition of heteroatom doped GQDs by various characterization techniques such as high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS) are also described. The recent progress on the impact of mono or co-doping of heteroatoms on PL behavior, and optical, electrochemiluminescence (ECL), and electrochemical properties of GQDs is also surveyed. Further, heteroatom doped GQDs with attractive properties used in sensing of various metal ions, biomolecules, small organic molecules, etc. by using various techniques with different limits of detection are also summarized. This review provides progressive trends in the development of heteroatom doped GQDs and their various applications.